2022
DOI: 10.3389/fpls.2022.928760
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enzymes in the Phthalide Biosynthetic Pathway in Angelica sinensis Using Integrative Metabolite Profiles and Transcriptome Analysis

Abstract: The roots of Angelica sinensis (Oliv.) Diels are well known for their efficacy in promoting blood circulation. Although many studies have indicated that phthalides are the main chemical components responsible for the pharmacological properties of A. sinensis, the phthalide biosynthetic pathway and enzymes that transform different phthalides are still poorly understood. We identified 108 potential candidate isoforms for phthalide accumulation using transcriptome and metabolite profile analyses. Then, six enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous studies have identified a key factor, phospho-2-dehydro-3-deoxyheptonate aldolase, that may be involved in accumulation of phthalides in A. sinensis [ 13 ]. Through expression profiling analysis, we found that the expression level of this gene was greater in unbolted samples than in bolted samples (Fig.…”
Section: Platform Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified a key factor, phospho-2-dehydro-3-deoxyheptonate aldolase, that may be involved in accumulation of phthalides in A. sinensis [ 13 ]. Through expression profiling analysis, we found that the expression level of this gene was greater in unbolted samples than in bolted samples (Fig.…”
Section: Platform Contentsmentioning
confidence: 99%
“…4 A). Furthermore, accumulation of phthalides significantly decreases after bolting [ 13 ]. Expression of this gene showed a trend similar to that of synthesis and accumulation of active compounds.…”
Section: Platform Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1) ( 19 , 20 ). However, other possible pathways for the phthalide scaffold formation could not be excluded ( 21 ), such as cyclization of 12-C fatty acid (fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…Angelica sinensis (Oliv.) Diels (Umbelliferae) (A. sinensis) is a biennial medicinal plant that thrives in cold and damp hillside areas in regions at elevated altitudes between 2200 and 3000 m [1,2]. Min County in the Gansu Province of China is the largest A. sinensis production area, accounting for 70% of China's total production [3].…”
Section: Introductionmentioning
confidence: 99%